2020
DOI: 10.3390/brainsci10010028
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Core Regions for Path Integration on Medial Entorhinal Cortex of Hippocampal Formation

Abstract: Path integration is one of the functions that support the self-localization ability of animals. Path integration outputs position information after an animal’s movement when initial-position and movement information is input. The core region responsible for this function has been identified as the medial entorhinal cortex (MEC), which is part of the hippocampal formation that constitutes the limbic system. However, a more specific core region has not yet been identified. This research aims to clarify the detai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 114 publications
(162 reference statements)
0
8
0
Order By: Relevance
“…We report that the nanostructures of the right hippocampus CA1 revealed by TEM display neuronal injury, which includes mitochondrial swelling, disruption, and autolysis in HFD fed animals which was subsequently worsened by UCMS. The hippocampus, a vital structure of the limbic system [ 19 ], exhibits a close relationship with emotion, memory, and learning and is vulnerable to mental stress [ 20 , 21 ], owing to its association with the HPA axis [ 22 ]. The hippocampus is divided into CA1, CA2, CA3, and dentate gyrus (DG).…”
Section: Discussionmentioning
confidence: 99%
“…We report that the nanostructures of the right hippocampus CA1 revealed by TEM display neuronal injury, which includes mitochondrial swelling, disruption, and autolysis in HFD fed animals which was subsequently worsened by UCMS. The hippocampus, a vital structure of the limbic system [ 19 ], exhibits a close relationship with emotion, memory, and learning and is vulnerable to mental stress [ 20 , 21 ], owing to its association with the HPA axis [ 22 ]. The hippocampus is divided into CA1, CA2, CA3, and dentate gyrus (DG).…”
Section: Discussionmentioning
confidence: 99%
“…The processing of egocentric spatial relations is mediated by medial superior-posterior areas, whereas allocentric spatial coding requires an additional involvement of the right parietal cortex, the ventral visual stream and the hippocampal formation (Zaehle et al, 2007). In a recent review of path integration representation in the hippocampus, the authors suggested that landmark identification and distance estimation relative to an internal map are presumably slower perceptual and cognitive processes than the mathematical integration of acceleration/ velocity signals, which can be produced in thalamic or primary sensory areas and partly during sensory transduction (e.g., with vestibular inputs) (Fukawa et al, 2020). This may be related to our results observed in the present study showing a reduced decision time for detouring when using body-motion cue.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we developed the structureconstrained interface decomposition (SCID) method that can design HCDs that complement this information, consistent with the findings of neuroscience. Researchers with a certain level of expertise in both information processing and neuroscience can use this method to efficiently design BRA (Fukawa et al, 2020;Yamakawa, 2020a).…”
Section: Brainmentioning
confidence: 99%
“…A-2) refinement of each region such as hippocampus, cerebellar, and amygdala: Detailed correspondence regarding the hippocampus is in progress (Taniguchi et al, 2021a;Fukawa et al, 2020).…”
Section: Roadmapmentioning
confidence: 99%